Scientific productions about ethnic-racial issues present in School Notebooks (Research, Society and Development, 2021)
This article is an excerpt an ongoing research in the scope of the Graduate Program in Science and Humanities Teaching – PPGECH of the Federal University of Amazonas, Brazil, Academic Unit of Humaitá/AM (UFAM/IEAA), research, in which, the main objective was to analyze the ethnic-racial issues presente in the student’s notebooks, whose contents refer to the early years of elementary school. In this clipping, we raise some scientific productions in the Digital Library of Theses and Dissertations (BDTD) that focused on the investigation, the applicability of Law 11,645/2008 in the school contentes of the early years of elementary school and research that had school notebooks as empirical material in their analyzes and which contained the theme put in focus here. The theoretical lenses used in this approach are supported by the perspectives of the prefix “Post”, that is, Post-Critical, Post-Modern, Post-Colonial, Cultural Studies (EC), Studies on Race, and other studies that articulate with the perspectives “post” as the Modernity/Coloniality Group. The results indicate that, based on the identified works, there are many gaps letf when it comes to the applicability of Law 11,645/2008 in school contents registered in the student’s notebooks.